Residual astigmatism following cataract surgery (Anwer Khan Modern Medical College Journal, 2021)
Objective: To determine the amount of residual astigmatism following cataract surgery.Materials and methods: A hospital based observational study was conducted in a tertiary eye hospital, Bangladesh during the period of July, 2013 to June, 2014. Patients was selected for the study who diagnosed as ARC with variable amount of astigmatism (1.5 to 3.5D), and excluded any other ocular pathology or history of previous ocular surgery. Phacoemulsification with PC Toric IOL implantation in all cases. Auto refracto-keratometer was done Preoperative and postoperatively for assessing the astigmatism. Main outcome measured were included preoperative uncorrected visual acuity, postoperative uncorrected visual acuity on 1stPOD, after 1 week and 1month, Preoperative keratometry, Preoperative astigmatism, Postoperative uncorrected keratometry on 1st POD, after 1 week and 1month, Postoperative uncorrected astigmatism on 1stPOD, after 1 week and 1monthResults: 30 eyes of 28 patients were assessed in this study. Due to clear corneal incision during phacoemulsification, the steep meridian became flat significantly from pre-operative keratometry 44.329±1.473D (mean±SD) to 30thpost operative keratometry 43.971±1.431D (mean±SD) having p